Surgical Site Infections in Major Head and Neck Surgeries Involving Pedicled Flap Reconstruction. (January 2017) - Goyal, Neerav; Yarlagadda, Bharat B.; Deschler, Daniel G.; Emerick, Kevin S.; Lin, Derrick T.; Rich, Debbie L.; Rocco, James W.; Durand, Marlene L.
Objective: To evaluate surgical site infections (SSI) after pedicled reconstruction in head and neck surgery. Methods: Records of patients with pedicled flap reconstructions between 2009 and 2014 at Massachusetts Eye and Ear were reviewed. Onset of SSI or fistula ≤30 days postoperatively was noted. A free flap cohort was reviewed for comparison. Results: Two hundred and eight pedicled reconstructions were performed for cancer (83%), osteoradionecrosis (7%), and other reasons (10%). Most (72%) cases were clean-contaminated and American Society of Anesthesiologists classification 3 or higher (73%); 63% of patients had prior radiation. The SSIs occurred in 9.1% and were associated with a longer length of stay ( P = .004) but no particular risk factors. Seventeen patients developed a fistula (11 without SSI). The SSI rates were not significantly different between pedicled and free flaps, but pedicled flap patients were older, more likely to have had prior surgery and/or radiation, and be methicillin-resistant Staphylococcus aureus positive. In the combined population, multivariate analysis demonstrated clean-contaminated wound classification ( P = .03), longer operating time ( P = .03), and clindamycin prophylaxis ( P = .009) as SSI risk factors. Conclusions: The SSI rate following pedicled flap surgeries was low and similar to free flap surgeries despite a significantly different population. No specific risk factors were associated with developing a pedicled flap SSI.